Assessing potential trade-offs between the lower back and shoulders: influence of lift training intervention on joint demands. Issue 1 (2nd January 2022) - Ma, Karen Y.; Nadon, Alicia L.; McDonald, Alison C.; Dickerson, Clark R.
Abstract : Background. Many of the approaches available for modifying manual materials handling (MMH) exertion emphasize lower back protection but often do not consider how interventions affect other body regions. This study focused on the influence of lift training on resultant joint moments and muscular demand trade-offs between the lower back and shoulders during MMH tasks. Methods. Three recommended lifting techniques (straddle lift, pivot technique and tripod lift) were compared to a priori (untrained) self-selected lifting techniques. Results. Mean and cumulative resultant moments indicated that using the lifting techniques evaluated in this investigation protected the shoulders more than the lower back. Mean and peak shoulder muscle activity also decreased following training ( p  < 0.05). Although there were no peak and mean changes to lower back muscle activity ( p >0.05), there was a significant decrease in cumulative lower back muscle activity ( p  < 0.05). Reported perceived exertion values decreased following training across the lifting techniques for all evaluated body regions ( p  < 0.05). Conclusion. Overall, the recommended MMH techniques protected both the lower back and the shoulders, and no exposure trade-offs between them were identified.